Strategi Pengelolaan Konten TikTok dalam Layanan Informasi Publik oleh Humas Perumda Transportasi Pakuan Bogor - Akhila Dilan Ramadhan; Suparman Suparman (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the process of managing TikTok content as a public information service by the Public Relations of Perumda Transportasi Pakuan Bogor. The study used a descriptive qualitative approach, collecting data through participatory observation, in-depth interviews, documentation, and direct involvement of researchers in the Public Relations Division of Perumda Transportasi Pakuan Bogor. The research informants consisted of the deputy head and members of the Public Relations Division directly involved in TikTok content management. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that content management is carried out in four stages: planning, production, distribution, and evaluation. Content planning is based on social media trends, audience information needs, and TikTok insight data. Production involves filming, editing, and internal review before publication. Content distribution is carried out routinely, taking into account upload times and active audience interaction. Evaluation is conducted using TikTok insight data to measure audience engagement and content effectiveness. This study also identified obstacles such as rapidly changing TikTok trends, technical production constraints, and challenges in creating engaging yet informative content. Structured content management can support TikTok as a public information service that is communicative, effective, and easily understood by the public.